PERBEDAAN SEBELUM DAN SESUDAH PENERAPAN IFRS TERHADAP LABA BERSIH, EKUITAS DAN ABNORMAL RETURN SAHAM PADA PERUSAHAAN YANG GO PUBLIK DI BEI - Ira Febrianti (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
This study aims to determine the differences before and after the implementation of IFRS on the financial statements of companies listed on the Stock Exchange. By looking at the difference in net income, equity and abnormal stock returns to firms in Indonesia in the IFRS convergence process using the Event Window is analyzed with nonparametric statistics: two paired sample test - Wilcoxon Signed Rank Test. This research is a quantitative study that led to the investigation before and after the implementation of IFRS. The study population was all the companies listed on the Stock Exchange in 2011 and 2012. The research sample was determined using purposive and Judgement sampling, obtained 78 sample firms. The results showed that there are significant differences on net income, equity and firm abnormal stock returns after implementation of IFRS.Keywords: IFRS, net income, equity, abnormal stock return, net profit margin, return on equity, average abnormal stock returns.